(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
In modern higher education, ensuring the harmony of education and moral development has become an essential pedagogical task. Higher education institutions are expected not only to provide professional knowledge and skills but also to contribute to students’ moral, ethical, cultural, and social development. This article examines the pedagogical mechanisms that ensure the integration of education and moral upbringing in higher education. The study analyzes theoretical foundations, learner-centered approaches, value-based education, the role of teachers, curriculum integration, extracurricular activities, and the institutional environment. Special attention is given to innovative pedagogical methods that promote holistic personality development. The article argues that the effective harmony of education and moral development enhances students’ academic performance, social responsibility, and readiness for professional and civic life.